Brief Report: Body Mass Index and Cognitive Function Among HIV-1–Infected Individuals in China, India, and Nigeria. (1st February 2019) - Jumare, Jibreel; El-Kamary, Samer S.; Magder, Laurence; Hungerford, Laura; Umlauf, Anya; Franklin, Donald; Ghate, Manisha; Abimiku, Alash'le; Charurat, Man; Letendre, Scott; Ellis, Ronald J.; Mehendale, Sanjay; et al.
Abstract : Background: Risk of cognitive impairment is increased among persons with high or low body mass index in HIV− and HIV+ populations in resource-rich settings. We examined this association among HIV+ patients in 3 resource-limited settings. Methods: This secondary analysis included data of 761 HIV+ volunteers pooled from 3 prospective cohort studies conducted in China (n = 404; 53%), India (n = 200; 26%), and Nigeria (n = 157; 21%). World Health Organization (WHO) weight classifications were based on body mass index. T scores, adjusted for demographics and practice effects, were derived from a 7-domain neuropsychological battery. Neurocognitive impairment (NCI) was defined as global deficit score of ≥0.5. Results: Overall, prevalence of NCI at baseline was 27.7% (similar across all cohorts). The overweight/obese and underweight constituted 37.3% and 15.5% of the total participants, respectively. In a multivariable logistic regression of pooled longitudinal data, adjusting for clinical and demographic variables, the odds of global NCI were 38% higher among the overweight/obese as compared to normal weight participants [odds ratio: 1.38 (95% confidence interval: 1.1 to 1.72); P = 0.005]. Similarly, the odds of global NCI were 39% higher among the underweight as compared to normal weight participants [odds ratio: 1.39 (95% confidence interval: 1.03 to 1.87); P = 0.029]. Conclusions: NCI among HIV-1–infected patients was more prevalent in both overweight/obese and underweight than normal weight individuals in 3 resource-limited settings, confirming observations in resource-rich settings. Mechanisms underlying these associations are unclear but likely differ for underweight and overweight persons. Abstract : Supplemental Digital Content is Available in the Text.